Against the odds: exploring individuals’ pushback mechanisms against commercialized football gambling - Adebisi, Tunde; Aregbesola, Ayooluwa; Taiwo-Abdul, Timilehin (Frontiers in Public Health, 2024)
Introduction The need for money, the pursuit of pleasure, and the liberalized access to gambling have been documented in several pieces of literature as the drivers of gambling. Such drivers are predicated on commercialized gambling, leading to the growth of the gambling industry and constituting a structural influence that normalizes the activity among young people. Methods Through a qualitative inquiry, this study investigates the social agentic factors of individuals who are susceptible to gambling. Fifteen non-gamblers were recruited across three commercial cities in Africa, namely Nairobi, Lagos, and Johannesburg. We first established the gambling susceptibility of the participants: their need for money, their passion for football, ownership of a smartphone, access to the internet, and exposure to football gambling marketing. Results Consequently, we probed for their agency, which is indicative of why they do not gamble, despite being susceptible to engaging in the activity. Four major agentic factors were identified from the participants; knowledge of the industry’s business model, conserving the integrity of football, identity of self, morality and/or religion model. Discussion As such, these factors may be utilized to develop an intervention program for gamblers within the geographical context.